The Influence of Visual, Auditory, Kinesthetic (VAK) Learning Methods in Enhancing English Vocabulary for Students at MTs Nur-Rahma Kota Bengkulu - Nuriska, Nuriska; Zasrianita, Fera; Revola, Yashori (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of the Visual, Auditory, Kinesthetic (VAK) Learning method on the English vocabulary mastery of seventh-grade students at MTs Nur Rahma Kota Bengkulu. The research method used was quantitative with a pre-experimental design (One-Group Pretest-Posttest Design). The subjects of this study were 14 students of class VII Mekkah. Data were collected through vocabulary tests (pre-test and post-test) and analyzed using the Normality Test and Paired Sample t-Test with the assistance of SPSS version 27. The results of the study showed a significant improvement in students’ vocabulary mastery after the implementation of the VAK method. This was evidenced by the average post-test score (61.57) being higher than the average pre-test score (41.43), as well as the result of the paired sample t-test with a significance value (2-tailed) of 0.001 < 0.05. Therefore, it can be concluded that the Visual, Auditory, Kinesthetic (VAK) Learning method is effective in improving the English vocabulary mastery of seventh-grade students at MTs Nur Rahma Kota Bengkulu. g Methods in Enhancing English Vocabulary for Students at Mts Nur-Rahma Kota Bengkulu